The Use of Continuous Veno-Venous Hemodiafiltration in the Management of Ifosfamide-induced Encephalopathy: A Case Report. Issue 6 (August 2016) - Yeo, Kee Kiat; HaDuong, Josephine H.
Abstract : Encephalopathy is a common side effect of ifosfamide, occurring in up to 30% of patients. Although self-resolving in most cases, death secondary to severe encephalopathy has been reported. Methylene blue and thiamine have been occasionally successful as treatment. We report a case of an 11-year-old girl with relapsed neuroblastoma who developed grade 4 ifosfamide-induced encephalopathy. She showed no initial response to methylene blue and thiamine. She remained neurologically impaired and continuous veno-venous hemodiafiltration was started, with rapid resolution of encephalopathy. This is the first report of continuous veno-venous hemodiafiltration use for suspected ifosfamide-induced encephalopathy in the pediatric population.